2023
DOI: 10.1002/aelm.202300635
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vacancy Dynamics in Two‐Dimensional Memristive Devices

Benjamin Spetzler,
Dilara Abdel,
Frank Schwierz
et al.

Abstract: Two‐dimensional layered transition metal dichalcogenides (TMDCs) are promising memristive materials for neuromorphic computing systems. Despite extensive experimental work, the underlying switching mechanisms are still not understood, impeding progress in material and device functionality. This study reveals the dominant role of defect dynamics in the switching process of 2D TMDC materials. The switching process is governed by the formation and annihilation dynamics of a local vacancy depletion zone. It explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…These parameters critically determine the direction and symmetry of hysteresis in the I−V curve. 35 Bisht et al also reported on how electrical bias in one junction affects neighboring junctions due to graded point defects and their distribution in the inhomogeneous medium of hydrogen-doped nickelate films. 36 Raman, XPS, and KPFM investigations demonstrate the underlying nonhomogeneity and point defects (selenium vacancies) in WSe 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These parameters critically determine the direction and symmetry of hysteresis in the I−V curve. 35 Bisht et al also reported on how electrical bias in one junction affects neighboring junctions due to graded point defects and their distribution in the inhomogeneous medium of hydrogen-doped nickelate films. 36 Raman, XPS, and KPFM investigations demonstrate the underlying nonhomogeneity and point defects (selenium vacancies) in WSe 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the switching processes in the memory devices primarily stem from the number and location of structural defects and compositional impurities, high-resolution scanning transmission electron microscope (STEM) was employed to identify the defects at the edge and in the interior of the electrochemical exfoliated WSe 2 nanoflakes, as shown in Figure a,b. Four different types of defects, namely monoselenium vacancies (V Se ), diselenium vacancies (V 2Se ), W vacancies (V W ), and W adatoms (W ad ), were observed in the inner region of the exfoliated WSe 2 nanoflakes (Figure c–f).…”
Section: Resultsmentioning
confidence: 99%
“…As the tunnel transparency of the barrier is eliminated, the elastic tunneling is no longer the dominant transport mechanism, and the resistive properties of the ferroelectric film should also be taken into account together with polarization charge screening effects. By analogy with OxRAM [ 8–11 ] and 2D memristive devices [ 12 ] point defects are suggested to be responsible for the resistive switching in a FE‐memristor. It is hard to confirm this assumption since the concentration of the vacancies in a ferroelectric film is extremely low, complicating the direct identification of the defects and the establishment of their role in the resistive switching mechanisms.…”
Section: Introductionmentioning
confidence: 99%